Design of a Web-Based Information System for Battuta University Alumni Data Collection - Aisy Nst, Rihadatul; Syahputra, Dinur; Harahap, Baginda (PT. Technology Laboratories Indonesia (TechnoLabs), 2024)
The role of alumni data in supporting institutional development and fostering stronger connections between alumni and their alma mater is significant. Battuta University currently lacks an efficient system for collecting and managing alumni data, which has led to a gap in communication and potential missed opportunities for collaboration. This study aims to design a web-based information system tailored for the systematic collection, management, and utilization of alumni data. Using the System Development Life Cycle (SDLC) methodology, this research outlines each stage of system development, from requirements analysis to deployment. The proposed system features a user-friendly interface, secure data storage, and versatile data retrieval options, allowing administrators to update, manage, and access information effectively. The implementation of this system is expected to facilitate a more structured approach to alumni engagement, enhance communication between the university and its graduates, and support data-driven decision-making processes. This web-based solution is projected to improve the efficiency and reliability of alumni data management, contributing to the university’s strategic goals.